Selection criteria and yield stability in a large collection of African yam bean [Sphenostylis stenocarpa (Hochst ex. A. Rich) Harms] accessions - Olomitutu, O.E.; Abe, A.; Paliwal, R.; Abberton, M.; Oyatomi, O. (Cambridge University Press, 2025)
African yam bean (AYB) is an underutilized legume with significant potential for food security in sub-Saharan Africa, yet limited research exists on optimizing its seed yield through selective breeding. In this study, the seed yield (SY) performance and relative importance of some yield-related traits on SY in AYB were assessed. One hundred and ninety-six accessions of AYB were evaluated for 2 years in three agro-ecologies of Nigeria. The experimental design was a 14 × 14 lattice design with three replicates. Data were recorded on SY and 13 SY-related traits. Positive significant genotypic correlations were found between SY and 11 of these traits. Pod length (PL) had a negative significant relationship (rg = −0.44**) with SY. Path coefficient analysis identified days to maturity (DM), pod weight (PW), shelling percentage (SP), number of seeds per pod (NSPD), 100-seed weight (HSW) and seed thickness (ST) as traits with positive direct effects on SY. The additive main effect and multiplicative interaction analysis revealed highly significant accession, environment, accession × environment interaction and interaction principal components effects for SY. Accessions TSs-119, TSs-101, 138A, TSs-4, TSs-157A and TSs-61 were identified as superior and stable, and should be considered for further breeding purposes. Selection criteria for improved SY in AYB should include DM, PW, SP, NSPD, HSW and ST. The identified stable, high-yielding accessions and key yield-related traits provide a framework for accelerating AYB improvement across diverse agro-ecologies.